2016
DOI: 10.1038/bdjopen.2015.6
|View full text |Cite
|
Sign up to set email alerts
|

Cone-beam CT evaluation of root canal morphology of maxillary and mandibular premolars in a Turkish Cypriot population

Abstract: Objectives:Because of economic and political issues, Turkish Cypriots have been emigrating from Cyprus since the 1920s, especially to the United Kingdom, other European countries and Australia. Recently, according to the UK House of Commons, Home Affairs Committee, ~300,000 Cypriot Turks were living in the United Kingdom. However, this ethnic population residing in the United Kingdom has been insufficiently analysed. Although many Turkish Cypriots have been living abroad, little is known about the dental chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
44
1
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(49 citation statements)
references
References 28 publications
1
44
1
3
Order By: Relevance
“…reported that 1% of the examined first premolars presented two roots . Another study published on a Turkish population, published by Celikten et al., reported that a second root could be found in 3.6% of the 954 mandibular first premolars included in the investigation . In their review of the literature, Kottoor et al.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…reported that 1% of the examined first premolars presented two roots . Another study published on a Turkish population, published by Celikten et al., reported that a second root could be found in 3.6% of the 954 mandibular first premolars included in the investigation . In their review of the literature, Kottoor et al.…”
Section: Discussionmentioning
confidence: 96%
“…28 Another study published on a Turkish population, published by Celikten et al, reported that a second root could be found in 3.6% of the 954 mandibular first premolars included in the investigation. 29 In their review of the literature, Kottoor et al found significant differences among ethnic groups, reporting 2.52% of teeth with two roots among Caucasians (6226 teeth), 1% among Asians (2822 teeth), 16.2% among Africans or African Americans (812 teeth), and 6.67% among people from the Middle East (1200 teeth). 30 With regard to mandibular second premolars, we found a second root in 3.4% of teeth, which is comparable to the scientific literature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to a recent CBCT study by Abella et al [ 37 ] in Spanish population, in maxillary first premolars, the most prevalent root morphology observed was two rooted (51.4%) and most of the teeth exhibited Type IV canal configuration (52.8%), while in maxillary second premolars, the most prevalent root morphology seen was single rooted (82.9%) and most of these teeth exhibited Type I canal configuration (47.2%). Moreover, two-rooted maxillary first premolars were reported to be 33% with 51% having Type IV canal configuration in a Chinese population [ 41 ], 68.6% with 68% having Type I canal configuration in a Pakistani population [ 42 ], and 44.8% with 76.8% having Type IV canal configuration in a Turkish Cypriot population [ 43 ]. Additionally, single-rooted maxillary second premolars were reported to be 84% with 53.4% having Type I canal configuration in a Pakistani population [ 42 ], and Type I canal configuration was the most commonly observed in a Turkish Cypriot population (49.4%) [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…The rate of occurrence of a single canal ranges from 54 to 88.5%; however, multiple canals have been reported in 11.5-46% of cases [11] . C-shaped root canals have also been observed in mandibular first premolars, and their prevalence is reportedly 10-24% [12][13][14][15] .…”
mentioning
confidence: 99%